Intoxicação por chumbo em um cão - relato de caso - Palumbo, Mariana Isa Poci [UNESP]; Machado, Luiz Henrique de Araújo [UNESP]; Sakate, Michiko [UNESP]; Caetano, Daniela Fregni [UNESP]; Cagnini, Didier Quevedo [UNESP]; Amorim, Renée Laufer [UNESP] (My University, 2010)
The present study reports the occurrence of lead poisoning in a male, 2 year-old mongrel dog attended at UNESP Botucatu Veterinary Hospital. The animal was brought to the hospital with claim of gastrointestinal and nervous disturbs for 10 days, worsening in the last 24 hours. After unsuccessfully attempts to control status epileticus, the animal died. Hematological evaluation revealed significant rubricytosis and basophilic stippling, highly suggestive of lead poisoning. Serum lead concentration confirmed toxic levels of this element. Necropsy evidenced the presence of foreign bodies in stomach (one stone and two metallic objects) and, microscopically, characteristic inclusions in renal parenchyma. Fragments obtained from liver and kidneys revealed lead concentrations of 0, 8 μg/g and 25 μg/g, respectively, which in association to clinical signs of saturnism, determined the diagnosis of lead poisoning.
Lead poisoning in dog - case report
Keywords: Canines; Toxicology; Animalia; Canis familiaris